Colloidal-sized zirconium porphyrin metal–organic frameworks with improved peroxidase-mimicking catalytic activity, stability and dispersity. Issue 8 (4th March 2020) - Wang, Junning; Wei, Tianxiang; Liu, Yichen; Bao, Mengyuan; Feng, Rui; Qian, Yuxuan; Yang, Xue; Si, Ling; Dai, Zhihui
Abstract : A new and facile method was developed to synthesize a sub-100 nm zirconium porphyrin metal–organic framework with improved peroxidase-mimicking catalytic activity, stability and dispersity. Abstract : Metal–organic frameworks (MOFs) have attracted great attention as enzyme mimic materials in colorimetric hydrogen peroxide (H2 O2 ) detection. At present, it is highly desirable but remains challenging to prepare MOFs with high stability and dispersity to further improve their peroxidase-mimicking catalytic activity. In this work, we developed a new and facile method for the synthesis of a sub-100 nm peroxidase-mimicking zirconium porphyrin metal–organic framework (Zr-PorMOF) via a solvothermal method. The experimental results indicated that compared with the micron-sized crystals obtained using a classical synthesis method, the catalytic activity, stability and dispersity in water of the colloidal Zr-PorMOF were obviously enhanced. The as-synthesized colloidal Zr-PorMOF was further successfully applied in colorimetric H2 O2 detection, and satisfactory detection performance was obtained. Furthermore, the colloidal Zr-PorMOF was also successfully employed in the construction of a peroxidase-based tandem catalysis system. Taking glucose oxidase as an example, this system was successfully applied for glucose sensing in real human serum samples, which proved its practical feasibility in diabetes diagnosis and indicates its high potential feasibility in peroxidase-related applications in complex biomatrix.